Relationship between physician-patient interaction satisfaction with medication adherence in patients with type 2 diabetes on insulin in primary care / Nik Munirah Nik Mohd Nasir - Nik Mohd Nasir, Nik Munirah (2017)
Medication adherence has been found to be an important determinant in achieving glycaemic targets in Type 2 Diabetes (T2DM) patients. In other patient populations, physician-patient interaction satisfaction was found to influence medication adherence. It is then important to identify if this is also a factor amongst T2DM patients on insulin as poor adherence was associated with increased all-cause mortality. The general objective o f this study was to determine the relationship between physician-patient interaction satisfaction with medication adherence in patients with T2DM on insulin in the Malaysian primary care setting. This was a cross sectional study involving 197 T2DM patients on insulin from 2 government primary health clinics in Gombak. Physician-patient interaction satisfaction and medication adherence level were measured using validated questionnaires. Data analysis for descriptive, inferential and multivariate analysis statistics were performed. Overall satisfaction score was 42.1 out o f maximum 55. Factors associated with high satisfaction scores included younger age group, primary education level, pre-obese group and basal only insulin regime. For medication adherence, majority (48.2%) had low adherence score. Factors associated with medication adherence include ‘Interaction Outcome’ domain score and BMI. There is a positive correlation between ‘Interaction Outcome’ domain score and medication adherence score (r=0.283, p<0.001). There is a relationship between Interaction Outcome subdomain score with medication adherence. Increase in this subdomain score will result in an increase in medication adherence score. This study also found that there is an association between medication adherence and body mass index (BMI). Higher body mass index is associated with higher adherence level.